A systematic literature review of the types of authentication safety practices among internet users - Kovalan, Krishnapriyaa; Omar, Siti Zobidah; Tang, Lian; Bolong, Jusang; Abdullah, Rusli; Ahmad Ghazali, Akmar Hayati; Pitchan, Muhammad Adnan (SAI Organization, 2021)
The authentication system is one of the most important methods for maintaining information security in smart devices. There are many authentication methods, such as password authentication, biometric authentication, signature authentication, and so on, to protect cloud users’ data. However, online information is not yet effectively authenticated. The purpose of this systematic literature review is to examine the current types of authentication methods as a safety practices for information security among Internet users. The PRISMA method was adopted to present a systematic literature review of 28 articles from three main databases (20 articles from Scopus, one article from Google Scholar, and seven articles from Dimension). This study used the Prediction Study Risk of Bias Assessment Tool to appraise the quality of the included studies. From the findings of the study, a total of three main themes were identified: password authentication, biometric authentication, and multiple-factor authentication. Multiple-factor authentication was found to be the most secure and most frequently recommended authentication method. It is highly recommended to implement three-factor authentication and multi-biometric model in the future, as it provides a higher surveillance level in terms of information security among cloud computing users.